Dynamics of Learning in Neanderthals and Modern Humans Volume 1 2013
DOI: 10.1007/978-4-431-54511-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Neandertal-Modern Human Contact in Western Eurasia: Issues of Dating, Taxonomy, and Cultural Associations

Abstract: Supporting Assimilation views of Neandertal/modern human interaction, chronostratigraphic reasoning indicates that the "transitional" industries of Europe predate modern human immigration, in agreement with their association with Neandertals in the Châtelperronian at the Grotte du Renne and St.-Césaire. Supporting the Neandertals' species separateness and less developed cognition, those industries are alternatively claimed to relate to pioneer groups of modern humans; the latter would have been the true makers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 96 publications
(156 reference statements)
2
55
1
1
Order By: Relevance
“…Following Nigst and Haesaerts (Nigst and Haesaerts 2012, Table 2), AH3 would contain two sidescrapers and 12 Blaterally retouched blanks.^Among the latter, several could also correspond, based on the illustrations supplied, to sidescraper fragments. As previously pointed out (Zilhão 2013), sidescrapers are a rare occurrence in Early Aurignacian assemblages. However, the percentage they represent in AH3 would be, if the classifications are valid, at least ten times higher than in the Early Aurignacian of e.g., Geissenklösterle, in Germany, or the Abri Pataud, in France.…”
Section: Ah3: the Old Collectionsmentioning
confidence: 73%
See 2 more Smart Citations
“…Following Nigst and Haesaerts (Nigst and Haesaerts 2012, Table 2), AH3 would contain two sidescrapers and 12 Blaterally retouched blanks.^Among the latter, several could also correspond, based on the illustrations supplied, to sidescraper fragments. As previously pointed out (Zilhão 2013), sidescrapers are a rare occurrence in Early Aurignacian assemblages. However, the percentage they represent in AH3 would be, if the classifications are valid, at least ten times higher than in the Early Aurignacian of e.g., Geissenklösterle, in Germany, or the Abri Pataud, in France.…”
Section: Ah3: the Old Collectionsmentioning
confidence: 73%
“…Before resigning ourselves to the implication that we must begin again from scratch, it is therefore prudent to examine the soundness of the claim's empirical basis. The more so since, in the case of the comparable arguments put forth for another central European site, the Geissenklösterle (Higham et al 2012(Higham et al , 2014, it has already been shown that the available dating results in no way imply assigning to its Early Aurignacian occupations an age beyond Bnormal^ (Zilhão 2013;Discamps et al 2015).…”
Section: Willendorf II and Its Archeological Horizon Ah3mentioning
confidence: 99%
See 1 more Smart Citation
“…Radiocarbon dating has provided a large time span for level IV, ranging from 38.5 to 30.5 cal kyr BP, controversially interpreted as possible evidence of a late Neanderthal survival in southern Iberia (26,29,37). Such controversy does not appear to have significant implications for the dating of the engraving, which logically must be older than the oldest-and for this reason, probably also more reliable-14 C determination from level IV (38.5 cal kyr BP), obtained from a sample collected at the very bottom of this level.…”
Section: Significancementioning
confidence: 99%
“…Other factors contributing to the difficulty in testing the foregoing hypotheses include persistent uncertainties in the chronology of archaeological sites at the so called Middle-to-Upper Paleolithic transition in Europe (23)(24)(25) and in the taxonomic affiliation of their inhabitants during this period (26)(27)(28).…”
mentioning
confidence: 99%